The Political Reform - Pease García, Henry (2007)
This paper tries to propose a series of institutional changes with the aim of strengthening democracy in Peru. The author makes a diagnosis of the democratic weakness of the country, due to the lack of representation, the weakness and crisis in which political parties find themselves, as well as the exclusion of broad sectors of the population and the ineffectiveness of the state. Based on this assessment, the author proposes objectives for democratic political reform, consisting of improving the quality of representation, strengthening political parties, balancing the system of government and eradicating centralism. In this context, this article recommends a series of specific actions that translate into the reform of the electoral system, the moderation of presidentialism, party accountability, among other changes.